Combined dynamic contrast enhanced MRI parameter with clinical factors predict the survival of concurrent chemo-radiotherapy in patients with 2018 FIGO IIICr stage cervical cancer. Issue 141 (August 2021) - Qin, Fengying; Pang, Huiting; Ma, Jintao; Zhao, Mingli; Jiang, Xiran; Tong, Rui; Yu, Tao; Luo, Yahong; Dong, Yue
Highlights: DCE-MRI parameter combined with clinical factors can predict the survival of IIICr cervical cancer following CCRT. FIGO IIIC2r stage, K trans, ADCmin value were independent prognostic factors of IIICr stage cervical cancer following CCRT. For stage IIIC1r subgroup, K trans, ADCmin and site of positive lymph node >2 were independent prognostic factors. Abstract: Purpose: Combined clinical prognostic factors and magnetic resonance imaging (MRI) parameters on predicting the prognosis after concurrent chemo-radiotherapy (CCRT)in patients with 2018 International Federation of Gynecology and Obstetrics (FIGO) IIICr stage patients. Methods: A total of 117 patients with cervical cancer (2018 FIGO stage IIICr) who underwent CCRT were enrolled from Dec.2014 to Jul.2017. 47 patients developed outcome events, including 32 recurrences and 15 deaths. Clinical and MR parameters of primary tumors were analyzed, including apparent diffusion coefficient (ADC) values (ADCmean, ADCmin, and ADCmax ) and dynamic contrast-enhanced MRI (DCE-MRI) parameters (K trans, Kep, Ve ) were recorded. The short diameters of visible lymph nodes in the MRI and enhanced computed tomography (CT) images were measured. Progression-free survival (PFS) was compared by Kaplan-Meier analysis and independent predictors were identified using cox regression analysis. Results: The median PFS was 35 months (6–68 month). The 1-year and 3-year PFS rates were was 90.4 %, 74.4 %, respectively. Multivariate analysis showed that 2018 FIGOIIIC2r stage (HR 2.701, 95 %CI1.259to. 5.797; p = 0.011), K trans (HR 0.353;95 %CI 0.189 to 0.659; p = 0.001) and ADCmin (HR0.423, 95 %CI0.229to0.783; p = 0.006) were highly correlated with poor PFS. Conclusion: In conclusion, we have identified IIIC2r stage, K trans value and ADCmin value as the most important factors in evaluating the survival rate and prognosis of patients with stage IIICr cervical cancer. For stage IIIC1r subgroup, K trans, ADCmin value and site of positive lymph node >2 were independent prognostic factors.